Low-volume Plasma Exchange In Immune-mediated Neurological Diseases : A tertiary care center study - Shrestha, Aashish; Gajurel, Bikram Prasad; Karn, Ragesh; Ojha, Rajeev; Rajbhandari, Reema; Gautam, Niraj; Shahi, Sumit; Ghimire, Pukar; Panthee, Pradeep; Bijukchhe, Sanjeev M (Nepal Mediciti Medical Journal, 2022)
BACKGROUND The optimal cost benefit of standard plasma exchange (SPE) has not been met where most of the patients do not afford the treatment. As an alternative, low volume plasma exchange (LVPE) is cost-effective than SPE where albumin replacement is eliminated. The aim of this study was to analyse the efficacy and safety of LVPE in various Immune mediated neurological diseases (IMND). METHODS A hospital-based retrospective study was conducted in patients with IMND who were admitted in TUTH between October 15, 2020, and October 14, 2022. Hemodynamically stable patients over the age of 18 who met the plasma exchange criteria were eligible. Outcomes and treatment-related complications were studied separately for the different diseases. RESULTS Of the 29 patients enrolled, 3 had Myasthenia gravis (MG), 6 had Neuromyelitis optica spectrum disorder (NMOSD), 11 had Gullian Barre syndrome (GBS), 6 had Chronic inflammatory demyelinating polyneuropathy (CIDP), and 3 had Autoimmune encephalitis (AE). Patients with MG, GBS, and CIDP all showed statistically significant improvement in mRS scores from 2.3±0.6 to 0 (p value = 0.0198), 3.03±1.8 to 2.2±1.4 (p value=0.0046) and 2.5±1.4 to 1.8±1(p value=0.025) respectively by the time they were discharged following treatment. Two patients developed Deep vein thrombosis (DVT), and two developed anaphylaxis during the course of their treatment, although none deteriorated further while in the hospital. CONCLUSION LVPE was effective in MG, GBS and CIDP. Myasthenia crisis patients who re-quired mechanical ventilation demonstrated complete resolution with LVPE making it a potential life-saving alternative for those who cannot afford standard therapy.